Design of Energy Efficient & Sustainable Buildings for ISRO Data Centers Using E-Quest (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2024)
Saving energy is the same as producing new energy. Sustainable development has elevated the importance of energy performance and energy efficiency. Energy efficiency is a crucial part of sustainability, which includes all sectors of the economy from agriculture to manufacturing to services to infrastructure, including buildings used for business and research activities. Developing countries face unique difficulties in achieving sustainability because they must balance two phenomena that are diametrically opposed to one another: rapid economic growth and long-term prosperity. Commercial, information technology (IT), real estate development and construction are important economic drivers. Energy is, of course, a crucial consideration in these fields. In this research, we propose a design strategy for improving energy efficiency in an ISRO Data center by using sustainable green building technology [1]. This paper discusses the initiatives of ISRO in this direction. As maximum operation & maintenance cost of the buildings is due to electrical energy, this study shows how to design the most energy efficient institutional buildings for IMGEOS (Integrated Multi mission Ground Segment for Earth Observation satellites) of ISRO, Hyderabad. The research work discuses about the strategies / techniques to be considered since the planning & designing stage of the building infrastructure itself. This research gives the complete details of the materials with their detailed technical specifications and the methodology to be adopted, for achieving the required energy efficiency level in the data centers / similar IT infrastructure buildings. The research work also explains the process of finding & selecting the most energy efficient model by using different combination of green building materials, with respect to the base line model of ASHRAE using the e-Quest building simulation software and the results obtained thereof. Thus, this detailed research study investigates the process of designing the energy efficient data center buildings for ISRO in the context of emerging countries.